Oxford international primary english workbook for grade 5 - Barber, Alison (Karachi: Oxford university Press., 2022)
The Oxford International Primary English Workbook for Grade 5 provides targeted practice to reinforce the language skills taught in the Student Book. It offers a range of engaging exercises designed to strengthen students' understanding of reading, writing, grammar, and vocabulary. The workbook encourages critical thinking and creativity, allowing students to apply key concepts such as sentence construction, punctuation, and comprehension strategies. With varied activities, including word puzzles and writing tasks, the workbook supports independent learning, helping students build confidence and refine their language skills in preparation for more advanced levels of English.